2004
DOI: 10.1152/ajprenal.00384.2003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of claudin-7 and -8 along the mouse nephron

Abstract: Expression of claudin-7 and -8 along the mouse nephron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(157 citation statements)
references
References 49 publications
9
148
0
Order By: Relevance
“…Besides, Claudins have been described as essential modulators of paracellular permeability (Matter and Balda 2007;Günzel and Yu 2013). Claudin-8 is restricted to the proximal tubule (PST), distal tubule and collecting duct in the mouse nephron (Li et al 2004). In addition, Claudin-8 plays an important role in the paracellular cation barrier of the distal renal tubule (Hou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Claudins have been described as essential modulators of paracellular permeability (Matter and Balda 2007;Günzel and Yu 2013). Claudin-8 is restricted to the proximal tubule (PST), distal tubule and collecting duct in the mouse nephron (Li et al 2004). In addition, Claudin-8 plays an important role in the paracellular cation barrier of the distal renal tubule (Hou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CLDN8 is required for the paracellular Cl -channel in the collecting duct. Immunofluorescence analyses have shown that CLDN3 and 7 are also expressed in the collecting ducts of mouse and rat kidneys (12,14), although one study described CLDN7 in the collecting ducts as located primarily on the basolateral membrane (13). Both M-1 and mIMCD3 cells express endogenous CLDN3 and CLDN7.…”
Section: Mutagenesis Identifies a Locus Of Amino Acids Critical For Cmentioning
confidence: 99%
“…CLDN3, 4, 7, and 8 are expressed primarily along the ASDN (12)(13)(14). In cultured renal epithelial MDCK cells, CLDN4 or CLDN8 overexpression selectively decreased the permeability of cations through TJs, specifically to Na + , K + , H + , and ammonium (15,16).…”
mentioning
confidence: 99%
“…A striking example is claudin-7, which is predominantly basolateral in the connecting tubule and collecting duct (68), as it is in airway, intestinal, and epididymal epithelia (23,42,51). At least in the epididymis it is not polymerized into strands (51).…”
Section: Expression and Localization Of Claudins In The Kidneymentioning
confidence: 99%